A Matlab-Based Least-Squares Method For Processing Experimental Data In Physics Education (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This article examines the feasibility of using a MatLab application to approximate experimental data using the least-squares method. Examples are provided for linear, quadratic, and other relationships between physical quantities.